A taxonomic review of Sueus Murayama, 1951 ambrosia beetles (Coleoptera: Curculionidae: Scolytinae: Hyorrhynchini) aided by molecular phylogenetic analyses - Cognato, Anthony I.; Smith, Sarah M.; Schiffer, Matthew; Li, You (Zootaxa, 2024)
Four Sueus Murayama, 1951 species occur in Southeast Asia and Oceania. They all likely have a female-biased haplodiploid inbreeding mating system and feed on symbiotic ambrosia fungi. These life history traits increase the potential of adventive events. Indeed, Sueus has been recently discovered on the Caribbean island of Martinique. Morphological variation has been observed among some populations of Sueus niisimai (Eggers, 1926), which questioned species boundaries. Given the beetle’s potential economic importance, we provide a molecular phylogeny as a foundation for systematic study and review the status of the known species. We sequenced a total of 1117 nucleotides from mitochondrial COI and nuclear CAD genes for 25 specimens. Parsimony and Bayesian phylogenies were similar in topology and demonstrated the sister placement of S. granulatus (Eggers, 1936) to the other Sueus species, reciprocal monophyly of S. niisimai and S. pilosus (Eggers, 1936) status restored, the monophyly of S. obesus Browne, 1977 and elevated levels of nucleotide divergence (interspecific = 16–22%). Sueus chatterjeei Smith & Cognato sp. nov. (India) and Sueus insulanus Schiffer, Smith & Cognato sp. nov. (Papua New Guinea) are described. Hyorrhynchus granulatus Eggers, 1936 is removed from synonymy with Hyorrhynchus lewisi Blandford, 1894 and reinstated as a valid species, Sueus granulatus (Eggers, 1936) status restored, comb. nov. A key to the eight recognized species is given. In addition, the identity of the Martinique species is revised as S. pilosus. Geographic distribution of species and the potential existence of cryptic species are discussed.